Design Implemetation And Study Of A Code (DPC) Modulator And De-Modulator Using Matlab And Simulink - Karuppayah, Nitiabalan (Universiti Sains Malaysia, 2005)
This thesis presents a detailed study of linear Pulse Code Modulation and also Differential Pulse Code Modulation using SIMULINK. Theoretical coding concepts are discussed extensively, each providing examples to accommodate better understanding of both PCM and DPCM concept. Non-linear PCM and DPCM cases are not discussed in this thesis. Basic introduction for the proposed systems are explained together with introduction to SIMULINK program. A step-by-step explanation of each stage is provided, along with accompanying visual parameter fields in the APPENDIX section. Two types of test input signals are given to both constructed models; namely, a sine wave of 100 radians/second and a simple ramp function. Each stage of the blocks operations are studied in detail and the outputs are presented in graphical waveforms. Signal-to-Quantization Noise ratio is calculated for each system and compared. Arising problems, such as the need of amplitude equalization, during the implementation of these circuits are also mentioned, along with steps to overcome the mentioned irregularities and redundant results. Two types of tests can be done to reach the final conclusion; the first, an objective test, where SNR are calculated and graphical results are produced. The second test is a subjective test, where Mean Opinion Score (MOS) is obtained to verify whether the speech coding encoded is discernable to a human ear and determining the quality of the output. Differences between PCM and DPCM are stated based on the results obtained from the simulation of both systems; namely, in terms of bandwidth requirements, quantization noise, coding, simplicity of the implemented circuit, and also the quality of the output obtained.